Breast development and satisfaction in women with disorders/differences of sex development. Issue 12 (27th November 2019) - van de Grift, Tim C; Kreukels, Baudewijntje P C
Abstract: STUDY QUESTION: What are the levels of breast development and satisfaction in women with a Disorder/Difference of Sex Development (DSD)? SUMMARY ANSWER: Compared with normative data, women with DSD reached lower Tanner stages and reported less breast satisfaction. WHAT IS KNOWN ALREADY: Women with DSD may have chromosomal and hormonal variations that can impact typical breast development. While much emphasis is placed on genital development in this group, little is known about breast development, satisfaction and their association. STUDY DESIGN, SIZE, DURATION: Data collection was part of the cross-sectional European multicenter dsd-LIFE study. Fourteen recruiting sites included 1040 participants between February 2014 and September 2015. PARTICIPANTS/MATERIALS, SETTING, METHODS: A total of 695 female-identifying participants were included (Turner n  = 332, 46, XY DSD n  = 141 and congenital adrenal hyperplasia n  = 222), with a median age of 28 years. Clinical (i.e. history of hormone and surgical treatments, Tanner breast examination) and patient-reported (i.e. breast satisfaction, relationship status, sexual satisfaction and experienced femininity) data was collected by independent trained research staff. The relationship between breast development, satisfaction and femininity was assessed. Control data on breast development and satisfaction in women without DSD was retrieved from the literature. MAIN RESULTS AND THE ROLE OF CHANCE: Of the 695 participants, 61% had received estrogen replacement and 51% puberty induction therapy, whereas 2% had received breast augmentation surgery. Approximately 65% of participants had reached Tanner breast stage 5, which is substantially less than the general population (90%). Breast satisfaction was lower than normative data as well ( P  < 0.001, Cohen's d  = 0.45). Breast size and breast satisfaction were associated with feelings of femininity. LIMITATIONS, REASONS FOR CAUTION: Limitations include the sample representativeness (e.g. regarding the clinical heterogeneity) and the limited in-depth knowledge on (prior) hormonal regimens. Furthermore, no (matched) control data was collected as part of this study. WIDER IMPLICATIONS OF THE FINDINGS: In order to support the psychosexual well-being of women with DSD, enhancing breast development by sufficient hormone replacement and possible augmentation surgery is advocated. The scope of DSD management should be beyond genital development only and consider breasts as well. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by the European Union Seventh Framework Program (FP7/2007–2013) under grant agreement no. 305 373. There are no competing interests. TRIAL REGISTRATION NUMBER: German Clinical Trials Register: Registration identification number: DRKS00006072.